2011
DOI: 10.1111/j.1651-2227.2011.02411.x
|View full text |Cite
|
Sign up to set email alerts
|

Preschool wheeze – impact of early fish introduction and neonatal antibiotics

Abstract: Aim: The aim of this study was to analyse the risk factors for preschool wheeze with special reference to the early introduction of fish and early antibiotic treatment. To avoid reverse causation regarding antibiotics, we focused on the influence of broad-spectrum antibiotics given during the first week of life.Methods: Data were obtained from a prospective, longitudinal study of a cohort of children born in western Sweden where 50% of the birth cohort was randomly selected. The parents answered questionnaires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
81
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(90 citation statements)
references
References 30 publications
8
81
1
Order By: Relevance
“…Most studies have been carried out in older children or assessed the timing of introduction of fish in the infant' s diet rather than the amount of fish consumption afterward. However, Goksor et al 11 showed that early fish introduction, but not the frequency of fish consumption at 12 months, was associated with recurrent wheeze, which is in line with our results. Similar results were also found in the Prevention of Allergy Among Children in Trondheim study.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Most studies have been carried out in older children or assessed the timing of introduction of fish in the infant' s diet rather than the amount of fish consumption afterward. However, Goksor et al 11 showed that early fish introduction, but not the frequency of fish consumption at 12 months, was associated with recurrent wheeze, which is in line with our results. Similar results were also found in the Prevention of Allergy Among Children in Trondheim study.…”
Section: Discussionsupporting
confidence: 83%
“…Various studies have suggested that early life exposure of n-3 polyunsaturated fatty acids (n-3 PUFA), a major component in fatty fish, protects against the development of asthma. 2,9,10 In line with this, a recent study reported a beneficial effect of introduction of fish before age 9 months on the development of wheezing at age 4.5 years, 11 whereas another study reported no association between introduction of fish and asthma. 12 However, because fish can also be highly allergenic, 13 the optimal timing of introduction of fish in the infant' s diet and the adequate amount remains unclear.…”
Section: Discussionsupporting
confidence: 59%
“…Despite significant differences in clinical presentation, lung function and genetics between children with EVW and MTW phenotypes, there is a large overlap between the groups [16][17][18][19]. While some children retain a consistent pattern of EVW or MTW over longer periods, symptom patterns change over time in many [15].…”
Section: Distinguishing Between Evw and Mtwmentioning
confidence: 99%
“…Fish consumption in infancy has been studied as the time of introduction in some studies and as the frequency of intake in other studies. In most studies, fish in the child's diet has been associated with reduced risk of eczema, rhinitis, wheeze, and asthma up to preschool age (11)(12)(13)(14)(15)(16)(17)(18). However, there have also been reports of no association with allergic disease (19).…”
Section: Introductionmentioning
confidence: 94%
“…If such recommendations were followed, leading to delayed introduction and, thereby, a lower intake of fish in these children, this disease-related modification of exposure may bias studies on fish consumption in infancy. Therefore, most recent studies on early fish consumption have taken the disease-related modification of exposure into account in different ways (11,(13)(14)(15)(16)(17)(18). Today, such recommendations are not given (22,23), and fish is considered a healthy food.…”
Section: Introductionmentioning
confidence: 99%